Adjuvant treatment for triple-negative breast cancer: a retrospective study of immunotherapy with autologous cytokine-induced killer cells in 294 patients - Yuhan, Zhang; Shuaibing, Wang; Beibei, Yang; Su, Lu; Yiyi, Du; Hong, Liu (Cancer biology & medicine, 2019)
To examine the efficacy and safety of a sequential combination of chemotherapy and autologous cytokine-induced killer (CIK) cell treatment in triple-negative breast cancer (TNBC) patients. A total of 294 post-surgery TNBC patients participated in the research from January 1, 2009 to January 1, 2015. After adjuvant chemotherapy, autologous CIK cells were introduced in 147 cases (CIK group), while adjuvant chemotherapy alone was used to treat the remaining 147 cases (control group). The major endpoints of the investigation were the disease-free survival (DFS) and overall survival (OS). Additionally, the side effects of the treatment were evaluated. In the CIK group, the DFS and OS intervals of the patients were significantly longer than those of the control group (DFS: = 0.047; OS: = 0.007). The multivariate analysis demonstrated that the TNM (tumor-node-metastasis) stage and adjuvant CIK treatment were independent prognostic factors for both DFS [hazard ratio (HR) = 0.520, 95% confidence interval (CI):0.271-0.998, = 0.049; HR = 1.449, 95% CI:1.118-1.877, = 0.005, respectively] and OS (HR=0.414, 95% CI:0.190-0.903, = 0.027; HR = 1.581, 95% CI:1.204-2.077, = 0.001, respectively) in patients with TNBC. Additionally, longer DFS and OS intervals were associated with increased number of CIK treatment cycles (DFS: = 0.020; OS: = 0.040). The majority of the patients who benefitted from CIK cell therapy were relatively early-stage TNBC patients. Chemotherapy in combination with adjuvant CIK could be used to lower the relapse and metastasis rate, thus effectively extending the survival time of TNBC patients, especially those at early stages.